2017
DOI: 10.1371/journal.pone.0184668
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of strength exercises and effects of regular strength training on cell free DNA concentrations in blood plasma

Abstract: Creatine kinase (CK) is a marker for muscle cell damage with limited potential as marker for training load in strength training. Recent exercise studies identified cell free DNA (cfDNA) as a marker for aseptic inflammation and cell damage. Here we overserved in a pilot study the acute effects during strength exercise and chronic effects of regular strength training on cfDNA concentrations over a period of four weeks in three training groups applying conservation training (CT) at 60% of the 1 repetition maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Interestingly, bouts of strenuous exercise caused rapid increase in cell free DNA (cfDNA) concentration in plasma and, moreover, it was suggested to be a promising marker of acute exercise induced-metabolic changes in human body 3 . Exercise resulted in the surge of plasma cfDNA independently of workout associated with various sport disciplines and types of training such as weightlifting 4 , running 5 , soccer 6 , cycling 7 , rowing 8 , strength training 9 or repeated sprint 6 . Concentration of post-exercise cfDNA positively correlated with the duration and the intensity of aerobic running 10 as well as with selected markers of muscle damage 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, bouts of strenuous exercise caused rapid increase in cell free DNA (cfDNA) concentration in plasma and, moreover, it was suggested to be a promising marker of acute exercise induced-metabolic changes in human body 3 . Exercise resulted in the surge of plasma cfDNA independently of workout associated with various sport disciplines and types of training such as weightlifting 4 , running 5 , soccer 6 , cycling 7 , rowing 8 , strength training 9 or repeated sprint 6 . Concentration of post-exercise cfDNA positively correlated with the duration and the intensity of aerobic running 10 as well as with selected markers of muscle damage 11 .…”
Section: Introductionmentioning
confidence: 99%
“… Fatouros et al, 2006 subjected participants to four 3-week training blocks of varying intensity and found that cirDNA peaked during the highest volume of training and fell as training intensity was decreased. This is opposed by the finding of Tug et al, 2017b that neither low- nor high-intensity acute strength training showed significant association with cirDNA levels. In addition, the frequency of habitual exercise (ranging from 0 to 7 times a week) had no association with cirDNA levels in 14 healthy women ( Brodbeck et al, 2020 ).…”
Section: Lifestyle Factorsmentioning
confidence: 67%
“…No change in cirDNA levels was observed following a chronic intense running programme in male endurance runners ( de Sousa et al, 2012 ), resistance training in 23 (control group) and 27 (resistance training) elderly participants ( Tosevska et al, 2016 ) or 8 weightlifters ( Gentles et al, 2017 ). In contrast, two studies reported a significant cirDNA increase after performing resistance multi-joint exercises ( Fatouros et al, 2006 ) and a range of strength exercises ( Tug et al, 2017b ) in 17 recreationally and 16 regularly trained men, respectively. One study of male soccer players observed a significant mid-season cirDNA increase only in players who started games in autumn season ( A. Gentles et al, 2015 ).…”
Section: Lifestyle Factorsmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, it has been shown that cell-free DNA (cfDNA) is a pro-inflammatory load dependent marker of aerobic and strength exercise ( Breitbach et al, 2012 ; Haller et al, 2017 ). For strength training, elevated baseline cfDNA values have even been described as a potential marker for overtraining ( Fatouros et al, 2006 ) and have been reported to occur the first 2 days following strength exercise in unaccustomed participants, while acute responses accumulated over the course of strength exercise sets within 10–60 min ( Tug et al, 2017 ). Moreover, cfDNA has been implicated as an early predictor of muscle performance decrement following muscle damage ( Andreatta et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%